1978
DOI: 10.1002/bjs.1800650816
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative treatment of retained bile duct calculi in patients with an indwelling T tube

Abstract: The results of combined instrumental and chemical treatment of retained bile duct calculi in 18 patients with an indwelling T tube are reported. The instrumental extraction of stones was carried out through the T tube channel using a modified Dormia apparatus. The chemical method involved continuous infusion through the T tube of heparin in saline alternating with sodium cholate. The treatment was successful in 16 of 18 patients with from 1 to 14 residual stones. The instrumental extraction of stones is recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This study indicates female preponderance as observed in the present study. Brown JE and Christensen C , 1967 [7] , in their study on 104 patients who underwent a primary operation for biliary tract disease included 19 male patients and 85 female; females accounting for majority (85%), similar to current study.The clinical features in our study like pain in right hypochondrium (80%), fatty dyspepsia (72.5%), vomiting (30%), fever with chills (15%) and jaundice (10%) are in accordance with studies by Chetlin SH and Elliot DW ,1971 [8]andWells GR, Taylor EW, Lindsay G, et al 1989 [9] .In the present study, USG proven choledocholithiasis was the commonest indication for CBD exploration (80%), with cholelithiasis with previous history of jaundice (10%) as second most common symptom. Previous CBD stenting with retained stones (5%) and intraoperative palpable stones in CBD (5%) were other indications.…”
Section: Discussionsupporting
confidence: 63%
“…This study indicates female preponderance as observed in the present study. Brown JE and Christensen C , 1967 [7] , in their study on 104 patients who underwent a primary operation for biliary tract disease included 19 male patients and 85 female; females accounting for majority (85%), similar to current study.The clinical features in our study like pain in right hypochondrium (80%), fatty dyspepsia (72.5%), vomiting (30%), fever with chills (15%) and jaundice (10%) are in accordance with studies by Chetlin SH and Elliot DW ,1971 [8]andWells GR, Taylor EW, Lindsay G, et al 1989 [9] .In the present study, USG proven choledocholithiasis was the commonest indication for CBD exploration (80%), with cholelithiasis with previous history of jaundice (10%) as second most common symptom. Previous CBD stenting with retained stones (5%) and intraoperative palpable stones in CBD (5%) were other indications.…”
Section: Discussionsupporting
confidence: 63%
“…Chande and Devitt (1973) suggested primary closure of the choledochotomy as they had shown a higher morbidity in patients with T tubes. With increasing success in dissolving stories with solutions infused down T tubes (Gardner et al, 1975;Chary, 1977) or by removal with a modified Dormia basket (Christiansen et al, 1978), we feel that T tube drainage should still be used after supraduodenal explorations. Endoscopists are also obtaining good results in the treatment of stones in the common bile duct by endoscopic sphincterotomy and basket extraction.…”
Section: Discussionmentioning
confidence: 99%